The Three-Terminal Interactive Lossy Source Coding Problem - Rey Vega, Leonardo; Piantanida, Pablo; Hero, Alfred O. (IEEE transactions on information theory, 2017)
In this paper, we explore the three-node multiterminal lossy source coding problem, which seems to offer a formidable mathematical complexity. We derive an inner bound to the general rate-distortion region of this problem, which is a natural extension of the seminal work by Kaspi on the interactive two-terminal source coding problem. It is shown that this (rather involved) inner bound contains several rate-distortion regions of some relevant source coding settings. In this way, besides the non-trivial extension of the interactive two terminal problem, our results can be seen as a generalization and hence unification of several previous works in the field. By specializing the inner bound to particular cases, we obtain some novel rate-distortion regions for several multi-terminal lossy source coding problems.